The Effect of Molecular Orientation in Disperse Red-1 Film on Its Refractive Index. Issue 1 (1st June 2022) - Herman, H.; Narayana, I.G.; Hidayat, R.
Abstract: The refractive index of materials is an important physical quantity in the design of various photonic devices. For thin-film based devices, the fabrication method should be compatible with existing processes in microelectronic fabrication and allow for controlling the refractive index. In this research, the material used is a polar Disperse Red 1 (DR1) molecule. The film fabrication was carried out using the physical vapor deposition method which had been equipped with an electric poling installation. The poling of the electric field during the deposition process was applied perpendicular to the substrate. The thickness measurement and the refractive index of the films were carried out using a reflectometer where the light was incident perpendicular to the substrate. The refractive index was determined by the multiple beam interference method. As a result, it was found that the application of an electric field causes a change in the orientation of the molecules, which were initially parallel to the substrate to become perpendicular. Increasing the field strength further reduces the number of molecules parallel to the substrate. This correlates with a decrease in the refractive index of the film.